The Bite of the Honeybee: 2-Heptanone Secreted from Honeybee Mandibles during a Bite Acts as a Local Anaesthetic in Insects and Mammals - Papachristoforou, Alexandros; Kagiava, Alexia; Papaefthimiou, Chrisovalantis; Termentzi, Aikaterini; Fokialakis, Nikolas; Skaltsounis, Alexios-Leandros; Watkins, Max; Arnold, Gerard; Theophilidis, George (My University, 2012)
Honeybees secrete 2-heptanone (2-H) from their mandibular glands when they bite. Researchers have identified several possible functions: 2-H could act as an alarm pheromone to recruit guards and soldiers, it could act as a chemical marker, or it could have some other function. The actual role of 2-H in honeybee behaviour remains unresolved. In this study, we show that 2-H acts as an anaesthetic in small arthropods, such as wax moth larva (WML) and Varroa mites, which are paralysed after a honeybee bite. We demonstrated that honeybee mandibles can penetrate the cuticle of WML, introducing less than one nanolitre of 2-H into the WML open circulatory system and causing instantaneous anaesthetization that lasts for a few minutes. The first indication that 2-H acts as a local anaesthetic was that its effect on larval response, inhibition and recovery is very similar to that of lidocaine. We compared the inhibitory effects of 2-H and lidocaine on voltage-gated sodium channels. Although both compounds blocked the hNav1.6 and hNav1.2 channels, lidocaine was slightly more effective, 2.82 times, on hNav.6. In contrast, when the two compounds were tested using an ex vivo preparation-the isolated rat sciatic nerve-the function of the two compounds was so similar that we were able to definitively classify 2-H as a local anaesthetic. Using the same method, we showed that 2-H has the fastest inhibitory effect of all alkyl-ketones tested, including the isomers 3- and 4-heptanone. This suggests that natural selection may have favoured 2-H over other, similar compounds because of the associated fitness advantages it confers. Our results reveal a previously unknown role of 2-H in honeybee defensive behaviour and due to its minor neurotoxicity show potential for developing a new local anaesthetic from a natural product, which could be used in human and veterinary medicine.
Keywords: Rat sciatic-nerve; Other Engineering and Technologies; Apis-mellifera-carnica; Varroa-destructor; Sodium-channels; In-vitro; Neurotoxicity; Pheromones